Performance Evaluation of the Effect of waste paper on Groundnut Shell Briquette - Oyelaran, Olatunde A; Bolaji, Bukola O; Waheed, Mufutau A; Adekunle, Micheal F (International Journal of Renewable Energy Development, 2015)
Current energy shortage and environmental issues resulting from the use of fossil fuels have lead to exploitation of renewable energy resources that includes municipal waste and agricultural residues. These residues are available, indigenous and are environmental friendly but some can not be used directly in combustion process due high moisture content and low volumetric energy unless by briquetting. The study was undertaken to assess the combustion characteristic of binderless briquettes produced from waste paper and groundnut shell. Combustion characteristics investigated were ignition time, burning time, calorific values, burning rate, specific fuel consumption, fuel efficiency and water boiling time. The calorific values of the briquettes ranged from 19.51 - 19.92 MJ/kg, while the thermal efficiency ranges between 13.75 – 21.64%, other results shows that the average burning rate between 0.511 and 1.133 kg/hr and the specific fuel consumption ranges between 0.087 and 0.131 J/g. The recorded boiling time values were between 17.5 and 30.0 minutes for cold start and 15.0 and 20.0 minutes for hot start. The results shows that waste paper and groundnut shell up to 25% in composition composite briquettes were found to have good combustion characteristics which qualify them as alternative to firewood for domestic and industrial energy. However, production of briquettes from waste paper and groundnut shell at mixing ratio of 85:15 was found to comparatively better from all experiment conducted.